Johdanto: Aktivistinen musiikintutkimus - Välimäki Susanna; Torvinen Juha; Mononen Sini (Tutkimusyhdistys Suoni ry, 2022)
The article discusses activist music research, i.e., praxis-oriented music research which deals with questions of societal and environmental justice.
Musiikki muutosvoimana: Aktivistisen musiikintutkimuksen manifesti